Clonal proliferations of cells infected with Epstein–Barr virus in preinvasive lesions related to nasopharyngeal carcinoma - Pathmanathan, Rajadurai; Prasad, Umapati; Sadler, Robert; Flynn, Kathryn; Raab-Traub, Nancy (Massachusetts Medical Society, 1995)
Background: The Epstein-Barr virus (EBV) is consistently detected in patients with nasopharyngeal carcinoma. To determine whether EBV infection is an early, initiating event in the development of this malignant tumor, we screened nasopharyngeal-biopsy samples, most of which were archival, for preinvasive lesions, including dysplasia and carcinoma in situ. Preinvasive lesions were found in 11 samples, which were tested for the presence of EBV.